Droplets on patterned substrates: Water off a beetle's back - Dupuis, A; Yeomans, J (2006)
We present a lattice Boltzmann model to describe the spreading of droplets on chemically and topologically patterned substrates. As an example, we consider the process by which a Namibian beetle captures water on its back which is hydrophobic but covered by peaks with hydrophilic tops. Copyright © 2005 John Wiley and Sons, Ltd.